INNOVATIVE METHODS IN TEACHING FOREIGN LANGUAGES FOR STUDENTS OF NON-LANGUAGE UNIVERSITIES (ResearchJet Journal of Analysis and Inventions, 2021)
This article analyzes modern methods of developing English language skills in university students. Measures to teach English in a unique way for students of non-philological disciplines using new technologies